A new species of Polana (Angusana) (Hemiptera: Cicadellidae: Gyponini): new record, key to males and description of the female terminalia of Polana exornata - Domahovski, Alexandre Cruz; Cavichioli, Rodney Ramiro (Zootaxa, 2022)
The subgenus Angusana is newly recorded from Brazil with description of a new species, Polana (Angusana) eliasi sp. nov. from State of Rondônia. Polana (Angusana) exornata is recorded from Costa Rica and the female terminalia is described and illustrated for the first time. A revised diagnosis and key to males of Angusana are provided.